Regulation of the protein glycosylation pathway in yeast: structural control of N-linked oligosaccharide elongation. - Gopal, P K (1987)
The yeast Saccharomyces cerevisiae X2180 strain with the mnn1 mnn2 mnn9 mutations, all of which affect mannoprotein glycosylation, synthesizes N-linked oligosaccharides having the following structure: (Formula: see text) whereas the mnn1 mnn2 mutant extends the alpha 1----6-linked backbone of some of the core oligosaccharides by adding 20-30 mannose units. Membrane fractions from the mnn1 mnn2 and mnn1 mnn2 mnn9 mutants are equally effective in catalyzing transfer from GDP-[3H]mannose to add mannose in both alpha 1----2 and alpha 1----6 linkages to an oligosaccharide having the following structure: (Formula: see text) but neither membrane preparation can utilize the homologous mnn1 mnn2 mnn9 oligosaccharide as an acceptor. Thus, addition of the alpha 1----2-linked mannose side chain to the terminal alpha 1----6-linked mannose in oligosaccharides of the mnn9 mutant inhibits the elongation reaction and may serve as an important structural control of mannoprotein glycosylation. The mnn9 mutation also increases the transit time for invertase secretion, meaning that this mutation could affect the processing machinery in the Golgi apparatus.